VARIABEL-VARIABEL YANG MENENTUKAN TINGKAT PROFITABILITAS BANK - Devi Anggarini, Ni Putu; Sedana, Ida Bagus Panji (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.05.TAHUN 2018DO - 10.24843/EEB.2018.v07.i05.p04, 2018)
This research was conducted at BPR in Bali Province. Data in this research is financial ratio and financial report of BPR period year 2012-2015. Sampling technique in this research by using census method Independent variable in research that is CAR, NPL, LDR, and BOPO. Dependent variable is profitability financial ratios with ROA indicator. Data analysis in this research use discriminant analysis technique. Based on the discriminant test using simultance, the Unstandardized Canonical Discriminant Function model can classify two groups of BPR based on their discriminant value appropriately by 79% of the total sample. The result of this research shows that LDR and BOPO have positive and significant influence on the level of Profitability. CAR and NPL have no significant effect on Profitability level. Operational Cost of Operating Income (BOPO) is the most dominant financial ratios to differentiate bank profitability. So the bank management is expected to be more effective and efficient in managing its operational costs. Further research can examine other financial variables.